Fighting mad : resisting the end of Roe v. Wade - Littlejohn, Krystale E., 1985-; Solinger, Rickie, 1947- (University of California Press, 2024)
"Fighting Mad is a book about what "reproductive justice" means and what it looks like to fight for it. Editors Krystale E. Littlejohn and Rickie Solinger bring together many of the strongest, most resistant voices in the country to describe the impacts of the Supreme Court's Dobbs decision and what it means for abortion access and care. The essayists and change agents in Fighting Mad represent a remarkable breadth of expertise: activists and artists, academics and abortion storytellers, health care professionals and legislators, clinic directors and lawyers, and so many more. They discuss abortion restrictions and strategies to provide care, the impacts of criminalization, efforts to protect the targeted, shortcomings of the past, and visions for the next generation. Fighting Mad captures for the social and historical record the vigorous resistance happening in the early post-Roe moment to show that there are millions on the ground fighting to secure a better future"-- Provided by publisher.
Keywords: Abortion -- Law and legislation -- United States.; Reproductive rights -- United States.; Pro-choice movement -- United States.; Droits génésiques -- États-Unis.; Mouvement pour la libéralisation de l'avortement -- États-Unis.; Legal History.; LAW.; Women's Studies.; SOCIAL SCIENCE.; Gender Studies.; Abortion -- Law and legislation.; Pro-choice movement.; Reproductive rights.; United States.